The Strategic Role of Teachers in Enhancing Learning Effectiveness through Optimal Classroom Management - Erin Anggraeni; Nurul Istiqomah; Vianur Riska; Abdurrahmansyah Abdurrahmansyah (Peneliti.net, 2026)
Teachers play a strategic role in determining the effectiveness of learning and students’ academic success. They are not only responsible for delivering instructional material but also act as facilitators, motivators, classroom managers, and evaluators in the learning process. This article aims to analyze the strategic role of teachers in improving learning effectiveness through the implementation of optimal classroom management. The method used is a literature review by examining various relevant scientific sources related to teacher professionalism, instructional strategies, and classroom management. The findings indicate that learning effectiveness is influenced by teachers’ ability to create a conducive learning environment, apply approaches that align with students’ characteristics, and implement active, innovative, creative, effective, and enjoyable learning strategies. Furthermore, well-planned classroom management through organized learning environments, positive discipline reinforcement, and a humanistic emotional approach has been proven to enhance students’ motivation, participation, and learning outcomes. Therefore, optimizing the teacher’s role supported by effective classroom management becomes a key factor in improving the quality of both the learning process and its outcomes in a sustainable manner